48.3: Stress Model Simulation of TFT reliability for G8.6 large‐size TFT‐LCDs. (4th October 2019) - Mo, Qiong-hua; Cho, An-Thung; Lin, Chun-Yan; Hsu, James; Chen, Wade; Lu, York; Fan, Xiao-bin; Scott,; Wu, Li-feng
Abstract : In this paper, Time‐sampling Simulation and lifetime calculation are both used to predict TFT reliability. The thin film transistor can be used to simulate and test the electrical properties of TFT devices according to the parameters measured many times. The simulation obtained by a lot of tests used to simulate and test the key points of TFT. In this way, we substitute the preset working parameters to save time. In this paper, Different insulating layer design of TFT device as an example has been investigated by stress simulation and TFT device lifetime has been predicted.